Homeworking in the Philippines: Bad job? Good job? - Amelita M. King-Dejardin (International Labour Organization (ILO), 2021)
This report focuses on two categories of homeworkers in the Philippines: industrial homeworkers, who assemble or fabricate goods for factories, retailers or their agents under subcontracting arrangements; and online workers, who render services to their clients or employers via telecommunications technologies and digital platforms. @This report focuses on two categories of homeworkers in the Philippines: industrial homeworkers, who assemble or fabricate goods for factories, retailers or their agents under subcontracting arrangements; and online workers, who render services to their clients or employers via telecommunications technologies and digital platforms. Using new data generated from focused group discussions and interviews with industrial homeworkers, an online survey of online "freelance" workers, and interviews with key informants, this report provides valuable insights into workers' motivations for engaging in homework, patterns of employment relationships, and working conditions, while comparing the two types of homework, and female and male workers. Entry into homework remains gendered. Child care and family care continue to be the principal driving force for women regardless of income level and educational attainment. Women dominate industrial and digital homework, even as many men take up online work as a principal occupation due to its flexible work schedule and higher pay. Issues of job insecurity, precarious and irregular earnings, exclusion from statutory health insurance and social security, disguised employer-employee relationships, and lack of legal recourse for non-payment of wages cut across both types of homeworking. Fairly high salaries and output-based payments coexist with meagre and volatile earnings in online work, while poverty wages are the mainstay of industrial homework. The value to women of earning, no matter how small, while caring for their children and family cannot be ignored. For them, this is vital and empowering. Nonetheless, the absence of effective governance that ensures homeworkers of fair working conditions and income security, combined with the lack of alternative care support and arrangements, exposes women and men to risks of exploitation, robs them of bargaining power, and traps many in poor quality jobs. An appropriate governance framework for homework is indispensable but not sufficient. Through self- organization and collective action, homeworkers can demand for better governance and State action, claim their legal rights, raise their bargaining position, and minimize a race to the bottom among their ranks.
Keywords: 330; precarious employment; self employment; non-standard forms of employment; digital labour; work at home; informal economy; gig economy